2001
DOI: 10.2176/nmc.41.271
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Aneurysms at the A1 Segment of the Anterior Cerebral Artery. Two Case Reports.

Abstract: Two rare cases of dissections which involve the anterior cerebral artery (ACA) are reported. A 58-yearold woman presented with a ruptured dissecting aneurysm manifesting as sudden onset of severe headache and consciousness disturbance followed by aphasia, right hemiparesis, paresis of the left lower extremity, and choreoathetotic movements of the upper arms and face. Computed tomography and angiography revealed subarachnoid hemorrhage due to a dissecting aneurysm at the left A 1 segment. The dissecting aneurys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…To begin with, intracranial arterial lesions are more common in Asian patients than in non-Asian patients [19,20,21]. With respect to ACA dissection causing brain ischemia, the case reports that were published were almost exclusively from Japan [8,22,23,24,25,26,27,28,29]. However, another explanation for the difference may be that ACA dissection may not have been diligently sought and may have been underdiagnosed in the previous studies [1,2,3,4,5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To begin with, intracranial arterial lesions are more common in Asian patients than in non-Asian patients [19,20,21]. With respect to ACA dissection causing brain ischemia, the case reports that were published were almost exclusively from Japan [8,22,23,24,25,26,27,28,29]. However, another explanation for the difference may be that ACA dissection may not have been diligently sought and may have been underdiagnosed in the previous studies [1,2,3,4,5].…”
Section: Discussionmentioning
confidence: 99%
“…However, since the ACA is narrow and curved, small dissections may be hard to accurately diagnose. Advances in high quality diagnostic imaging techniques, such as MRA and 3D-RA, may provide a basis for accurate diagnosis of the dissection [8,22,23,24,25,26,27,28,29]. In particular, 3D-RA provides precise depiction of the intracranial vasculature, including aneurysms [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the double lumen sign, which is visible fl ow in both the true and false lumen [6] , has been suggested to be a pathognomonic, it is rarely seen in intracranial arteries [1] . To the best of our knowledge, only 4 cases of the double lumen sign in the ACA have been reported in the English literature [7][8][9] . Kazui et al [10] reported 17 patients with solitary infarction in the territory of the ACA, including 4 of undetermined etiology.…”
Section: Discussionmentioning
confidence: 99%
“…If there is a high risk of rebleeding (rebleeding under conservative treatment, growing dissecting aneurysm, giant dissecting aneurysm, traumatic dissecting aneurysm or dissection associated with uncontrolled hypertension), direct treatment of the dissection might be proposed. Several surgical techniques have been attempted such as wrapping [16,21,22,25] , trapping with [3] or without [6,8,11,17,19,20,23,26] bypass surgery or clipping of the aneurysmal bulge [11,16] . The endovascular treatment consists in proximal occlusion, obstruction of the aneurysmal bulge or stent placement [13] .…”
Section: Discussionmentioning
confidence: 99%